Endovascular treatment of distal anterior cerebral artery aneurysms using flow modulation devices: mid- and long-term results from a two-center study - Khanafer, Ali; Henkes, Hans; Cohen, Jose; Albiña-Palmarola, Pablo; Gomori, John Moshe; Forsting, Michael; von Gottberg, Philipp (Frontiers in Neurology, 2024)
Purpose Flow-diverter (FD) stents have become an established treatment for intracranial aneurysms in recent years, but their use for aneurysms in distal cerebral vessels with small carrier vessel diameters remains controversial. This study describes the method and mid- and long-term outcomes of FD treatment of distal anterior cerebral artery aneurysms (DACAAs) at two neurointerventional centers, to elucidate this topic and provide more in-depth data. Methods Data for all patients at two neurointerventional centers who were treated with FDs for DACAAs in the pericallosal and supracallosal segment of the anterior cerebral artery were retrospectively analyzed. Data on periprocedural complications, and short-, mid- and long-term follow-up findings were recorded. Results Forty-one patients were eligible for inclusion in the study. Three FD models were used, one of which had an anti-thrombotic coating. Two periprocedural complications (5%) occurred but did not cause a change in the mRS. In the long-term follow-up, at 29 months and beyond, 83% of assessable patients showed complete occlusion of the aneurysms without new neurological deficits. Conclusion FDs are a safe and effective treatment approach for DACAAs. This study indicated a low risk of complications, and high closure rates in short-, mid- and long-term follow-up.